Developing health systems research capacities through north-south partnership: An evaluation of collaboration with South Africa and Thailand - Pitayarangsarit Siriwan; Doherty Jane; Mayhew Susannah H (BMC, 2008)
Abstract Background Over the past ten years, calls to strengthen health systems research capacities in low and middle income countries have increased. One mechanism for capacity development is the partnering of northern and southern institutions. However, detailed case-studies of north-south partnerships, at least in the domain of health systems research, remain limited. This study aims to evaluate the partnerships developed between the Health Economics and Financing Programme of the London School of Hygiene and Tropical Medicine and three research partners in South Africa and Thailand to strengthen health economics-related research capacity. Methods Data from programme documents were collected over five years to measure quantitative indicators of capacity development. Qualitative data were obtained from 25 in-depth interviews with programme staff from South Africa, Thailand and London. Results and Discussion Five years of formal partnership resulted in substantial strengthening of individual research skills and moderate instituonalised strengthening in southern partner institutions. Activities included joint proposals, research and articles, staff exchange and post-graduate training. In Thailand, individual capacities were built through post-graduate training and the partner institution developed this as part of a package aimed at retaining young researchers at the institution. In South Africa, local post-graduate teaching programs were strengthened, regular staff visits/exchanges initiated and maintained and funding secured for several large-scale, multi-partner projects. These activities could not have been achieved without good personal relationships between members of the partner institutions, built on trust developed over twenty years. In South Africa, a critical factor was the joint appointment of a London staff member on long-term secondment to one of the partner institutions. Conclusion As partnerships mature the needs of partners change and new challenges emerge. Partners' differing research priorities (national v international; policy-led v academic-led) need to be balanced and equitable funding mechanisms developed recognising the needs and constraints faced by both southern and northern partners. Institutionalising partnerships (through long-term development of trust, engagement of a broad range of staff in joint activities and joint appointment of staff), and developing responsive mechanisms for governing these partnerships (through regular joint negotiation of research priorities and funding issues), can address these challenges in mutually acceptable ways. Indeed, by late 2005 the partnership under scrutiny in this paper had evolved into a wider consortium involving additional partners, more explicit mechanisms for managing institutional relationships and some core funding for partners. Most importantly, this study has shown that it is possible for long-term north-south partnership commitments to yield fruit and to strengthen the capacities of public health research and training institutions in less developed countries.